2013
DOI: 10.21273/horttech.23.6.836
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dikegulac Sodium Applied to Pruned and Unpruned ‘Limelight’ Hydrangea Grown at Two Locations in the Southeastern United States

Abstract: Pruning is commonly performed during production of nursery crops to produce symmetrical, compact plants that are pleasing to the consumer’s eye. To achieve the desired results, nursery growers hand prune or apply plant growth regulators (PGRs). However, hand pruning is expensive and is not always effective, and efficacy of PGRs can depend on cultural practices, environmental conditions, irrigation, cultivar, and rate. Therefore, the objective of these experiments was to evaluate the effect of dikegulac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The highest concentrations of DS decreased inflorescence numbers. Similar results were found in unpruned panicle hydrangea (Cochran et al, 2013), where the plants treated with 1600 ppm DS had fewer branches and flowers compared with lower concentrations of DS. However, following application of 1600 ppm DS in bougainvillea (Bougainvillea) flower numbers increased (Norcini et al, 1993(Norcini et al, , 1994.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The highest concentrations of DS decreased inflorescence numbers. Similar results were found in unpruned panicle hydrangea (Cochran et al, 2013), where the plants treated with 1600 ppm DS had fewer branches and flowers compared with lower concentrations of DS. However, following application of 1600 ppm DS in bougainvillea (Bougainvillea) flower numbers increased (Norcini et al, 1993(Norcini et al, , 1994.…”
Section: Resultssupporting
confidence: 81%
“…Plants treated with 800, 1600, and 2400 ppm DS had shorter inflorescences than the control plants (Table 1). Cochran et al (2013) reported DS at 800 and 1600 ppm reduced inflorescence length of panicle hydrangea. Treatment with 1600 ppm DS to garden phlox (Phlox paniculata) plants resulted in shorter flower stalk height compared with the control (Grossman et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hand pruning and plant growth regulators (PGRs) are currently used to control plant growth and to promote increased branching (Cochran et al 2013). Hand pruning is time consuming and is labor intensive, leading to increased production costs (Holland et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hand pruning is time consuming and is labor intensive, leading to increased production costs (Holland et al 2007). Plant growth regulators may be effective, but their efficacy may vary across ornamental plant species, environmental conditions, substrates, irrigation practices, and method of application (Cochran et al 2013, Cole et al 2013, Keever 2003, Kessler and Keever 2008. Potential restrictions on the use of PGRs in some countries (Clifford et al 2004), and growing concerns about agrochemical use in plant production and their presence in runoff, are causing an increased interest in alternative means of plant growth control (Kaufmann et al 2000).…”
Section: Introductionmentioning
confidence: 99%